Perceptions of "others, " risk, and counter terrorism-related informal social control. Issue 3 (September 2019) - Fay, Suzanna; Crutchfield, Robert
Anti-terrorism messages associate immigration and minorities with terrorism even if this link is not explicit. The consequence is the potential for racial profiling of minorities as threats to national security. Recent experiences or threats of domestic terrorism, in Australia, the US, and other industrialized countries, have led policy makers to encourage informal social control in terrorism prevention efforts by appealing to citizens to report suspicious behavior to authorities. The linking of ethnically different "others"—members of Australia's population who are or are perceived to be outsiders to the mainstream—and terrorism is important because who is seen as threatening effects whether individuals engage in informal social control; the willingness of residents to recognize, intervene, and report suspicious behavior. However, the concept of "others" in relation to informal social control is more complicated than just immigration status and ethnic identity alone. This study examines whether perceptions of "others" are related to perceptions of terrorism risk and perceptions of informal social control in reporting national security threats.